Multiwavelength light emitters for scanning applications fabricated by flipchip bonding - Hofstetter, Daniel; Sun, D.; Dunnrowicz, Clarence; Kneissl, Michael; Treat, D.W. (My University, 1998)
We present a multiwavelength light source which was fabricated using a self-aligned flipchip bonding technique. The device consists of an InGaN-GaN light-emitting diode emitting light at around 420 nm, on top of which we flipchip-bonded a monolithically integrated red/infrared dual-beam laser. The upper two lasers were built by selective removal of the red laser, and subsequent regrowth of an infrared laser structure. Since all processes, including the deposition of the PbSn solder bumps for bonding, were based on photolithographic precision, tight alignment tolerances of ±μm in the lateral direction could be fulfilled between the ridge waveguides of the three light emitters. For a high-speed color scanning system, this is an important design criterion because it will allow the use of a single scanning optics for the three laser beams.
Keywords: flipchip-bonding; hybrid integration; lateral alignment; multiwavelength light emitters